Family-based, healthy living intervention for children with overweight and obesity and their families: a 'real world' trial protocol using a randomised wait list control design. Issue 10 (31st October 2019) - Liu, Sam; Marques, Isabela Gouveia; Perdew, Megan A; Strange, Karen; Hartrick, Teresa; Weismiller, Joy; Ball, Geoff D C; Mâsse, Louise C; Rhodes, Ryan; Naylor, Patti-Jean
Abstract : Introduction: Family-based behavioural weight management interventions are efficacious and widely used to address childhood obesity. Curriculum and strategies vary extensively and scale-up often depends on ensuring that the intervention fits the adoption context. Aims and objectives: To evaluate the impact and implementation of a 'made in British Columbia' (BC) family-based early intervention programme (EIP) for 8–12 years old with overweight and obesity and their families. Methods and analysis: A randomised waitlist-control trial will assess a 10-week interactive, family-based lifestyle intervention followed by four maintenance sessions, in BC, Canada. We aim to enrol 186 families. The blended intervention includes at least 26 contact hours between participants and programme providers, including interactive activities and educational materials through weekly 90-min group sessions, an online family portal, and self-directed family activities. Curricular content includes information and activities related to healthy eating, physical activity (PA), positive mental health, parenting practices and sleep hygiene. The waitlist control group will receive a modified programme with the same 10-week sessions in the family portal, and four group sessions. Families participate in data collection at baseline, postintervention (week 10) and follow-up (week 18). The primary outcome is to assess changes in child body mass index z-score at 10 weeks between the groups. Secondary outcomes include changes at 10 weeks between the groups in child and parent PA behaviour and skills, healthy eating behaviour, and mental health. Process evaluation will address reach, implementation and maintenance (baseline, 10-week and 18-week) using recruitment tracking forms, parent questionnaire, programme attendance tracking forms, leader feedback surveys, parents and children satisfaction surveys and postprogramme interviews with facilitators, stakeholders and parents. Intention-to-treat analyses will be conducted. Process evaluation will be analysed thematically. Ethics and dissemination: Study procedures were designed to address research and community needs and will follow ethical standards. Trial registration number: NCT03643341 .